An introduction to Timed Sequential Machines. (March 2014) - Giambiasi, Norbert
This paper introduces the Timed Sequential Machine (TSM) formalism. The TSM formalism is based on well-known sequential machines. It is less expressive than the Discrete Event System Specification formalism or Timed Automata, and it offers a set of concepts well adapted to intermediate abstraction levels that appear in the design or analysis processes of discrete event systems. In addition, timed extensions of testing and simplification methods for sequential machines can be defined and used in finite-state TSMs. After presenting the formal definition of a TSM and its behavior, methods are proposed for the minimization of completely specified finite-state TSMs and for the simplification of incompletely specified finite-state TSMs. Finally, it is demonstrated that the TSM formalism has the property of being closed under coupling. That is, any coupled TSM model can be described in terms of an atomic TSM model.